Organizacja dekanalna w diecezji kieleckiej w latach 1925-1939 - Bujak, Grzegorz (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The article discusses the changes which took place in the organisation of deaneries in the Diocese of Kielce in the years 1925-1939. These changes were caused by the necessity of adaptation to the new boundaries of the diocese which were introduced after the concordat of 1925 and the dynamic development of the city of Kielce. With regard to the creation of the deanery of Wiślica, the author presented the decision making process done by the administration of the diocese.